2001
DOI: 10.1136/jcp.54.9.664
|View full text |Cite
|
Sign up to set email alerts
|

D-Dimer testing: the role of the clinical laboratory in the diagnosis of pulmonary embolism

Abstract: Pulmonary embolism is a common, yet often unsuspected and unrecognised disease associated with a high mortality. New, objective, "user friendly" and cost eVective diagnostic strategies are being explored. D-Dimers, the fibrinolytic degradation products of crosslinked fibrin, have emerged as the most useful of the procoagulant activity and ongoing fibrinolysis markers. D-Dimer measurements are very sensitive in excluding a diagnosis of pulmonary embolism in the setting of normal values, a low clinical suspicion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…No significant differences were found in PTR during pregnancy, but were seen in APTTR corroborating a general trend in reduction reported previously [8]. There was also confirmation that fibrinogen levels increased as pregnancy continued [9,10].…”
supporting
confidence: 78%
“…No significant differences were found in PTR during pregnancy, but were seen in APTTR corroborating a general trend in reduction reported previously [8]. There was also confirmation that fibrinogen levels increased as pregnancy continued [9,10].…”
supporting
confidence: 78%
“…Most importantly, in patients who are considered to be clinically unlikely to have a DVT and who have a negative D‐dimer, the diagnosis of DVT is safely excluded, indicating an absence of false‐negative results using the D‐dimer test in such patients. Similar findings have also been found in studies examining the usefulness of the D‐dimer test in human patients with pulmonary thromboembolism (PTE) 17,18 . Recently, D‐dimer testing has been examined in various thromboembolic diseases in dogs, primarily dogs with PTE, with a negative test being considered a strong indicator of the absence of a thromboembolic disease.…”
Section: Introductionsupporting
confidence: 70%
“…This included dogs with neoplasia, liver disease, renal failure and post‐surgery 19–21 . For these reasons, the recommended cut‐off value for a positive D‐dimer using this assay has been suggested to be at >500 ng/mL in dogs as well as in humans 15,18,19,23 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, some individuals in whom inflammation is already causing hypercoagulability, as expressed by high D-dimer levels, will have values below 200 ng/mL. Since other studies have used cut-off thresholds that are even higher than the threshold used in our study, the amount of misclassification is probably even higher (2, 8–10). Consistent with results from previous studies, we found that the level of D-dimer as well as the prevalence of elevated D-dimer increases with age (2, 4, 10, 11).…”
Section: Discussionmentioning
confidence: 74%